2000
DOI: 10.1016/s0022-2275(20)32002-2
|View full text |Cite
|
Sign up to set email alerts
|

Sphingolipids and cholesterol modulate membrane susceptibility to cytosolic phospholipase A2

Abstract: Modulation of cytosolic phospholipase A 2 (cPLA 2 ) activity by sphingomyelin (SPH), ceramide (Cer), and cholesterol (Chol) was investigated in CHO-2B cells activated by the calcium ionophore A23187 and epinephrine. Chol depletion of CHO-2B cells by treatment with methyl-␤cyclodextrin (5 m M ) resulted in the inhibition of the release of arachidonic acid whereas the restoration of the level by Chol-loaded cyclodextrin relieved inhibition. Conversion of CHO-2B cellular SPH to Cer by Staphylococcus aureus sphing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2002
2002
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(4 citation statements)
references
References 49 publications
(63 reference statements)
0
4
0
Order By: Relevance
“…It is in accordance with our previous studies where SM was shown to decrease PLA 2 activity in different substrate-containing vesicles. 26,33 The activity of the enzyme (human recombinant cytosolic PLA 2 and human type II secretory PLA 2 ) was shown to be reduced in PC/SM containing mixtures compared to pure PC vesicles. In the present study, PLA 2 activity was examined as a function of the degree of fatty acid unsaturation.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is in accordance with our previous studies where SM was shown to decrease PLA 2 activity in different substrate-containing vesicles. 26,33 The activity of the enzyme (human recombinant cytosolic PLA 2 and human type II secretory PLA 2 ) was shown to be reduced in PC/SM containing mixtures compared to pure PC vesicles. In the present study, PLA 2 activity was examined as a function of the degree of fatty acid unsaturation.…”
Section: Resultsmentioning
confidence: 99%
“…Visualization of the coexisting phases was made possible by the use of the fluorescent lipid analogue egg Rhodamine-PE that preferentially partitions into L d phase. 33 When two liquid-disordered (L d ) and liquid-ordered (L o ) phases coexist in the plane of the membrane bilayer, the bright background is assigned to the L d phase, while the observed dark circular domains are assigned to the L o phase.…”
Section: Methodsmentioning
confidence: 99%
“…A recent report by Lee et al (10) showed that HDL from patients with Niemann-Pick disease, which contains a high concentration of SM, also exhibits impaired cholesterol esterification by LCAT and that this is mostly attributable to the lack of secretory SMase in these patients. However, studies with various phospholipases showed that ceramide, the product of SMase C reaction, is an independent activator of the phospholipases (12)(13)(14)(15)(16). Since LCAT is essentially a specialized phospholipase A that utilizes cholesterol as an acyl acceptor in place of water, this raised the possibility that the stimulation of LCAT reaction by SMase C treatment of lipoproteins is due to the formation of an activator (ceramide), rather than depletion of the inhibitor (SM).…”
Section: Discussionmentioning
confidence: 99%
“…Although the cellular functions of ceramide have been investigated well, its possible effects in the plasma compartment are unknown. Studies from several laboratories, including ours, have shown that ceramide is an activator of secretory and cytosolic phospholipases in vitro ( ). Because of its tendency to form inverted hexagonal phase structures (H II ), it disrupts the membrane bilayer ( , ), and this may be the basis for its activation of phospholipase activities.…”
mentioning
confidence: 98%